3D nanoscale imaging of amyloid-β oligomer interactions with extracellular vesicles by cryo-ET - Anum Khursheed; Qi Shang; Hui Zhang; Yao Tian; Piotr Szwedziak; Vladimir A. Volkov; John H. Viles (Proceedings of the National Academy of Sciences, 2026)
Central to Alzheimer’s disease pathology are prefibrillar oligomer assemblies of amyloid-β (Aβ) peptide. A widely discussed hypothesis proposes that amyloid-β oligomers insert into neuronal lipid membranes, disrupting their integrity and causing a loss of cellular homeostasis in Alzheimer’s disease. This membrane disruption is believed to be a major source of Aβ-induced neurotoxicity. Cryo electron tomography (cryo-ET) has facilitated 3D nanoscale imaging of Aβ-membrane interactions under near-native conditions. Analyses of small extracellular vesicles (sEVs) reveals that Aβ oligomers including annular and curvilinear extended oligomers (CLEOs) exhibit extensive binding to cell-derived lipid membranes, including insertion into and carpeting of the lipid bilayer. Notably, these oligomeric assemblies were also internalized and concentrated within the cell-derived exosomes and other small sEVs. Enrichment of Aβ oligomers within the vesicles typically ranged between 5 to 20 times the external Aβ levels depending on the vesicle size and curvature. In contrast, monomeric and fibrillar forms of Aβ displayed minimal membrane interaction. Once internalized CLEOs appear to be trapped in an oligomeric form and do not readily go on to form fibrils. Studies with vesicles of brain lipid extract indicate the Aβ internalization does not require the presence of a membrane protein. Our in vitro studies underscore the membrane-disruptive capacity of oligomeric Aβ species and suggest a role of sEVs in concentrating toxic Aβ oligomers and transporting oligomers across the brain interstitium.